Applicability of flexible photovoltaic modules onto membrane structures using grasshopper integrative model - Ibrahim, Hend; Wagdy, Ayman; Beccarelli, Paolo; Carpenter, Robert; Chilton, John (Elsevier, 2016)
The potentials of integrating thin-film photovoltaic technology into buildings make it the recommended renewable energy source not only for traditional architectures, but also the most innovative applications that favour envelopes characterized by free morphologies such as membrane structures. The integration of Photovoltaic technology into membrane structures offers a promising significant step in the market development. However, some challenges and questions are arising relating to the applicability of such systems and how they are significantly dependant on a list of complex aspects that have to be taken into account during the design phase. These aspects include the wide variety of membrane three-dimensional geometries that in turn govern the modules distribution, orientation and shadowing as well as the distribution of stresses and deflections for each single project and how both the structure and modules react to them.